Late onset invasive pneumococcal disease in a liver transplanted patient: beyond the Austrian syndrome. Issue 3 (14th April 2013) - Belvisi, V.; Del Borgo, C.; Morelli, F.; Marocco, R.; Tieghi, T.; Fabietti, P.; Vetica, A.; Lichtner, M.; Mastroianni, C.M.
Abstract Invasive disease caused by Streptococcus pneumoniae is a major cause of morbidity and mortality in high‐risk individuals with severe comorbidities, including asplenia, chronic alcoholism, and altered immune status. The risk of invasive pneumococcal disease has been significantly higher in transplant patients compared with the general population. Here, we report an unusual case of a disseminated pneumococcal infection with meningitis, endocarditis, spondylodiscitis, and muscle abscess in an asplenic patient on chronic immunosuppressive therapy for liver transplantation performed 17 years before.